Experimental Study of a Self-Determination Intervention for Youth in Foster Care. (August 2013) - Geenen, Sarah; Powers, Laurie E.; Powers, Jennifer; Cunningham, Miranda; McMahon, Lisa; Nelson, May; Dalton, Lawrence D.; Swank, Paul; Fullerton, Ann; ,
The aim of the study was to conduct a longitudinal, randomized clinical trial of the efficacy of TAKE CHARGE, a self-determination enhancement intervention, for promoting the school performance of youth in special education and foster care. A total of 133 youth were randomized to either a control group that received typical services, or to the intervention group that received coaching in the application of self-determination skills to achieve their goals, as well as participating in group mentoring workshops with successful young adult alumni of foster care. Findings on the outcomes of 123 youth who completed the study suggest gains for the intervention group in elements of self-determination, engagement in educational planning, school performance, and reduced anxiety and depression.